USULAN PERBAIKAN PERANCANGAN PRODUK SEPATU PERAWAT DENGAN PENDEKATAN METODE QUALITY FUNCTION DEPLOYMENT (QFD) - Dewi Shofi Mulyati; Nugraha Nugraha; Iyan Bachtiar (Faculty of Industrial Technology Universitas Islam Indonesia, 2016)
Shoes are footwears needed by everyone such as employees, housewives, students or any other profession to do their activity. One example of profession that wears shoes in doing their work is a nurse in the hospital. An intial observation done to the nurse profession in the hospital shows that there is a problem in the condition of the shoes they wear. The shoes condition is not suitable to the characterisctic of the work, as well as to the condition of the workplace enviroment, which could lead to fatigue to the nurses and significantly influence the stress level of the nurses. The study aims to design a shoes that meet the the consumers wishes and the ergonomic value which eventually could be proposed as the improvement design for the nurse shoes. The method used in this study is Quality Function Deployment (QFD) as a design method used to determine the priority needs and desires of consumers, as well as to classify them. From the data processing and analysing, it is shown that the innovation made in the shoes for nurses are on the material used, which previously used a cow skin and now it uses velvet, in order to reduce the production cost; the heel design of the shoes which is modified to be more varies to meet the nurse needs; the replacement on the soles materials so they would not be slippery and they would cost less.